Effect of Contaminants on the Performance of a Proton Exchange Membrane Fuel Cell. (7th August 2015) - Tavakoli, Bahareh; Weidner, John W.
Abstract : The overall cost and performance of proton exchange membrane fuel cells (PEMFCs) are an issue of tradeoffs, and the optimal design depends on the application. For example, avoiding degradation via contamination by using expensive materials increases the initial cost to produce the system, but it can extend life and improve the overall performance. This may be desirable where reliability is paramount. In contrast, using less expensive materials reduces the initial cost, but at the expense of the life-time cost of the system and reduced performance. A mathematical model was developed to quantify the performance loss and recovery of the fuel cell by the balance of plant contaminants. This analysis evolved from a systematic and collaborative investigation to understand, characterize, and quantify the degradation mechanisms due to contaminants that arise from components that make up the fuel-cell system. The degradation mechanisms, and the impact to PEMFC performance and durability of each compound was evaluated by infusion of that compound (i.e. 2, 6-diaminotoluene, benzyl alcohol, diethylene glycol monoethyl ether and diethylene glycol monoethyl ether acetate) to the cathode side of the fuel cell followed by measuring the fuel cell performance (i.e. current voltage curve, and high frequency impedance resistance).